Voorwoord: huldigingsbundel Prof. P.J. Strauss / Foreword: Festschrift Prof P. J. Strauss - S. D. Snyman (Acta Theologica)
From text: With this edition of Acta Theologica, we honour a colleague who amongst many other responsibilities and obligations, fulfilled his academic duties in presenting lectures for undergraduate students, study guidance to post-graduate students and publication of research findings in his field of interest.